Pengaruh Modal Kerja Dan Likuiditas Terhadap Kinerja Keuangan pada PT. Pertamina (Persero), Tbk - Nur Afni; Puji Muniarty; Aliah Pratiwi (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
This study aims to determine the “effect of working capital and liquidity on the financial performance of PT. Pertamina (Persero), Tbk from 2014 to 2023. Financial performance metrics include return on equity (ROE), current ratio (CR), and Working Capital Turnover (WCTO). CR measures liquidity, while WCTO measures working capital. To apply this quantitative technique, multiple linear regression analysis is used. The results showed that WCTO and CR had no significant effect on” ROE, either alone or in combination. A very small coefficient of determination (only 1% for working capital and liquidity) indicates that such factors do not significantly affect the financial success of the business. At PT. Pertamina (Persero), Tbk, the results showed that variables other than these two have a greater impact on ROE. This study suggests that companies should improve the efficiency of working capital management and optimal use of current assets in order to increase profitability.